2022
DOI: 10.26425/1816-4277-2022-2-71-76
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Industry 4.0 on the economy and production

Abstract: The difficulties and problems faced by economic entities, countries and regions, in general, on the way to implementing the achievements and developments of Industry 4.0 have been designated in the article. Special attention has been paid to economic and production aspects, as well as changes in the relevant systems in the context of radical technological transformations. In particular, it has been established that markets are becoming oligopolistic, the role and importance of medium and small businesses is si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…In India, the manufacturing and service sectors need more productivity and efficiency to manage these digital transformations (Jha 2021;Smolka and Papulova 2023). Researchers Kanji and Agrawal (2020) and Mezina et al (2022) found I4.0 may increase social inequality while creating a heightened need for highly qualified personnel. The authors argue that appropriate policies and partnerships need to be implemented to ensure inclusive development in developing countries, especially in India, Bangladesh, and Pakistan.…”
Section: South Asia and Industry 40mentioning
confidence: 99%
“…In India, the manufacturing and service sectors need more productivity and efficiency to manage these digital transformations (Jha 2021;Smolka and Papulova 2023). Researchers Kanji and Agrawal (2020) and Mezina et al (2022) found I4.0 may increase social inequality while creating a heightened need for highly qualified personnel. The authors argue that appropriate policies and partnerships need to be implemented to ensure inclusive development in developing countries, especially in India, Bangladesh, and Pakistan.…”
Section: South Asia and Industry 40mentioning
confidence: 99%
“…В связи с тем, что страна лишилась половины своих золотовалютных резервов и невозможностью взять кредит на внешних рынках, в ближайшие годы Правительству придется переориентировать ресурсы на наиболее значимые сферы, такие как оборона, социальная, финансовая и производственная. По заверениям правительства денег хватит на все ключевые направления и все значимые проекты будут реализованы, хотя, возможно, с приносом сроков реализации [7].…”
Section: рисунок 2 рост ввп россии по годам (%) (составлено авторами ...unclassified
“…Информационно-аналитическое финансовое издание «Банки сегодня» https://bankstoday.net (дата обращения 23.03.2023) 7. БКС Экспресс https://bcs-express.ru (дата обращения 23.03.2023).…”
unclassified